ANALISIS PENGARUH DAN DAMPAK PINJAMAN ONLINE TERHADAP GAYA HIDUP DAN PERILAKU KONSUMTIF PADA MAHASISWA FAKULTAS HUMANIORA PRODI HUKUM ANGKATAN TAHUN 2022 UNIVERSITAS SARI MULIA BANJARMASIN - Ratihpuspita Krisnowo; Mahendra Abdi Muhammad; Saputera Yandi (Law Department, University of Widya Gama Mahakam Samarinda, 2025)
This study aims to analyze the influence and impact of online loans on the lifestyle and consumer behavior of students, specifically the students of the Faculty of Humanities, Law Program, Class of 2022, at Sari Mulia University, Banjarmasin. Online loans have become increasingly popular among students due to their easy access and quick process, but they also raise concerns about their impact on students' financial behavior. The research method used is a qualitative survey with a sample of students from the Faculty of Humanities, Law Program, Class of 2022, at Sari Mulia University, Banjarmasin. Data were collected through an online questionnaire containing questions about the use of online loans, lifestyle, and consumption patterns.The results of the study show that the influence and impact of online loans on the lifestyle and consumer behavior of fifth-semester students from the Faculty of Humanities, Law Program at Sari Mulia University, Banjarmasin, do not significantly affect or change students' consumer behavior as a whole. This means that although online loans provide easy and fast access to funds, the study did not find strong evidence that these loans directly encourage students to adopt a higher or riskier consumer lifestyle. Several factors that may contribute to this neutral result include other variables affecting students' consumer behavior, such as income level, financial education, and self-control. Additionally, it is possible that students who use online loans may already have consumer habits before accessing these loans, so online loans are not considered the main factor in changing their behavior.Overall, this conclusion indicates that the influence of online loans on students' lifestyles and consumer behavior is complex and may be affected by many other factors. Therefore, further research may be necessary to better understand the conditions that influence the relationship between online loans and consumer behavior among students.